2004
DOI: 10.1038/sj.onc.1207826
|View full text |Cite
|
Sign up to set email alerts
|

A model for GFRα4 function and a potential modifying role in multiple endocrine neoplasia 2

Abstract: Mutations of the RET proto-oncogene are found in the majority of patients with the inherited cancer syndrome multiple endocrine neoplasia type 2 (MEN 2). A minority of cases, however, have no detectable RET mutation and there is considerable phenotypic variation within and among MEN 2 families with the same RET mutation, suggesting a role for other loci in this disease. A candidate for such a gene is glial cell line-derived neurotrophic factor receptor alpha 4 (GFRA4), which encodes a cell surfacebound co-rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Some other reports on FMTC families have speculated about the possible involvement of certain RET polymorphisms, such as L769L (c.2307T➝G, exon 13) or S836S (c. 2439C➝T, exon 14), in the reduced penetrance of the disease among carriers of mutations affecting the 804 codon (20,21). Results derived from a recent study revealed the over-representation or exclusive presentation of some variants within the GFRA4 gene (encoding a co-receptor of RET) in MEN 2 patients, when comparing with their healthy relatives, thus suggesting a putative modifying role for such polymorphisms in MEN 2 (22).…”
Section: Introductionmentioning
confidence: 99%
“…Some other reports on FMTC families have speculated about the possible involvement of certain RET polymorphisms, such as L769L (c.2307T➝G, exon 13) or S836S (c. 2439C➝T, exon 14), in the reduced penetrance of the disease among carriers of mutations affecting the 804 codon (20,21). Results derived from a recent study revealed the over-representation or exclusive presentation of some variants within the GFRA4 gene (encoding a co-receptor of RET) in MEN 2 patients, when comparing with their healthy relatives, thus suggesting a putative modifying role for such polymorphisms in MEN 2 (22).…”
Section: Introductionmentioning
confidence: 99%
“…These residues may be involved in the formation of intermolecular cysteine bridges, thereby giving rise to dimeric GFRa4 receptor complexes in the absence of PSPN (Figure 1e). Recently, a mutation that gives rise to two putative forms of soluble GFRa4 receptors was reported to be involved in a more aggressive disease course of MEN 2 (Vanhorne et al, 2005). As these mutated forms of the GFRa4 receptor also harbor non-conserved cysteine residues in D3 (Figure 1a), it remains to be determined if the described phenotype could be caused by the formation of covalently linked dimeric GFRa4 receptor complexes.…”
mentioning
confidence: 99%
“…A schematic picture of the mouse GFRa4 splicing variants is shown in Figure 1d. Recently, a mutation, which may contribute to a more aggressive disease course of MEN 2, was identified in human GFRa4 (Vanhorne et al, 2005). The mutation consists of a 7 bp insertion that causes a frameshift in all of the human GFRa4 splice variants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the intrafamilial and interfamilial phenotypic variability concerning the age of onset and tumor spectrum suggest that genetic modifying factors exist (5), and this has been confirmed using animal models (6). However, data on possible genetic factors involved in clinical MEN2 variability are scarce (7,8), which is partially due to the low prevalence of this syndrome (1:30,000; ref. 9).…”
Section: Introductionmentioning
confidence: 99%